Post-conflict reconstruction: seeds of hope help rebuild peace - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Poverty and inequality are major causes of tension and it is no coincidence that the majority of today s armed conflicts have countries of the South as their backdrop. But war also perpetuates poverty and hunger. ..